The functional and pathologic relevance of autophagy proteases - Fernández, Álvaro F.; López-Otín, Carlos (The Journal of Clinical Investigation, 2015)
Autophagy is a well-conserved catabolic process essential for cellular homeostasis. First described in yeast as an adaptive response to starvation, this pathway is also present in higher eukaryotes, where it is triggered by stress signals such as damaged organelles or pathogen infection. Autophagy is characterized at the cellular level by the engulfment of portions of the cytoplasm in double-membrane structures called autophagosomes. Autophagosomes fuse with lysosomes, resulting in degradation of the inner autophagosomal membrane and luminal content. This process is coordinated by complex molecular systems, including the ATG8 ubiquitin–like conjugation system and the ATG4 cysteine proteases, which are implicated in the formation, elongation, and fusion of these autophagic vesicles. In this Review, we focus on the diverse functional roles of the autophagins, a protease family formed by the four mammalian orthologs of yeast Atg4. We also address the dysfunctional expression of these proteases in several pathologic conditions such as cancer and inflammation and discuss potential therapies based on their modulation.